2014
DOI: 10.1111/curi.12066
|View full text |Cite
|
Sign up to set email alerts
|

Enacting Critical Literacy: The Case of a Language Minority Preservice Teacher

Abstract: This narrative study of an Asian female prospective teacher describes a language minority student's ways of enacting critical literacy in a teacher preparation program in the United States. It discusses how she exerted her agency despite her perceived marginalization as a non-native English speaker. The findings demonstrate how she resisted the identity imposed as a "slow learner" by an instructor while simultaneously challenging the tenets of critical literacy. Ultimately, the study suggests that personal nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Based on Freire's theoretical perspective, researchers like Wallace (2002), Cho (2014), Sanchez (2005), and Sullivan (2004) have applied critical pedagogy to develop critical thinking. Others have studied the role of discussion in developing critical thinking on the basis of social constructivism.…”
Section: The Role Of Discussion In Active Learningmentioning
confidence: 99%
“…Based on Freire's theoretical perspective, researchers like Wallace (2002), Cho (2014), Sanchez (2005), and Sullivan (2004) have applied critical pedagogy to develop critical thinking. Others have studied the role of discussion in developing critical thinking on the basis of social constructivism.…”
Section: The Role Of Discussion In Active Learningmentioning
confidence: 99%
“…Chun, 2009;Gómez Jiménez & Gutierrez, 2019;Gustine, 2018) or create an extracurricular activity for the enactment (e.g. H. Cho, 2014;Hayik, 2015aHayik, , 2015bHayik, , 2016.…”
Section: Curriculum and Standardsmentioning
confidence: 99%
“…Coulter, Michael & Poyner (2007) note that storytelling and narrative can be used both as a pedagogic strategy and as a research method, and they adopted both approaches in a study concerning English as a Second Language (ESL) and Bilingual teacher education. This has also been used by Cho (2014a;2014b), taking an autobiographical narrative approach to studies of 'language minority students', and by Saltmarsh (2012) in a collaborative biography activity. Moloney and Oguro (2015) found that, in linguistically diverse pre-service teachers, narrative enquiry elicited and represented affirmation of background and language skills, often for the first time in their university studies.…”
Section: Cald and Initial Teacher Educationmentioning
confidence: 99%